2016
DOI: 10.1152/physiolgenomics.00116.2015
|View full text |Cite
|
Sign up to set email alerts
|

Na/K-ATPase signaling regulates collagen synthesis through microRNA-29b-3p in cardiac fibroblasts

Abstract: Chronic kidney disease (CKD) is accompanied by cardiac fibrosis, hypertrophy, and dysfunction, which are commonly referred to as uremic cardiomyopathy. Our previous studies found that Na/K-ATPase ligands or 5/6th partial nephrectomy (PNx) induces cardiac fibrosis in rats and mice. The current study used in vitro and in vivo models to explore novel roles for microRNA in this mechanism of cardiac fibrosis formation. To accomplish this, we performed microRNA profiling with RT-qPCR based arrays on cardiac tissue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 52 publications
3
55
0
Order By: Relevance
“…Results from the miRTarBase using specific search strategy (keywords: “Bone marrow‐derived mesenchymal stem cells,” “microRNA,” “fibrosis” and “exosome”) showed that the 24 potential miRNAs target TGF‐β1 and might play role in anti‐fibrotic. After reviewing of pertinent literatures, we identified 6 miRNAs (mir‐29b‐3p, mir‐19b‐3p, mir‐130a‐3p, mir‐590‐5p, mir‐146a‐5p and mir‐181a‐5p) were reported have the potency of anti‐fibrotic in the liver, renal, cardiac and pulmonary tissue . Therefore, we envisage the possibility that such potential cargo microRNAs in EVs may involve in the anti‐fibrotic action in US development.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the miRTarBase using specific search strategy (keywords: “Bone marrow‐derived mesenchymal stem cells,” “microRNA,” “fibrosis” and “exosome”) showed that the 24 potential miRNAs target TGF‐β1 and might play role in anti‐fibrotic. After reviewing of pertinent literatures, we identified 6 miRNAs (mir‐29b‐3p, mir‐19b‐3p, mir‐130a‐3p, mir‐590‐5p, mir‐146a‐5p and mir‐181a‐5p) were reported have the potency of anti‐fibrotic in the liver, renal, cardiac and pulmonary tissue . Therefore, we envisage the possibility that such potential cargo microRNAs in EVs may involve in the anti‐fibrotic action in US development.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that miR-29b-3p as well as a set of other anti-fibrotic miRNAs were significantly decreased in cardiac tissues from rats subjected to PNx surgery [40]. The current study found that many of these anti-fibrotic miRNAs (miR-29b-3p, miR-20a-5p, and miR-19a-3p) were also decreased in the circulating exosome samples from both PNx and 2K1C animals, indicating that changes in exosomal miRNAs may reflect pathological changes in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic kidney disease (CKD), microRNA (miR)-29b-3p directly targets mRNA of collagen. Expression level of miR-29b-3p decreases in cardiac fibroblasts, which is regulated by Na/K-ATPase [36][37][38].…”
Section: Micrornasmentioning
confidence: 99%